Continuity without Essence: Death and Rebirth in Buddhism - Arca, Giovanni (Journal for the academic study of religion, 2025)
This article re-examines Buddhist accounts of death and rebirth through the lens of continuity without essence. Focusing on the Nikāyas while noting trajectories in Mahāyāna and Vajrayāna, it analyses how dependent origination, the five aggregates, and karmic causality articulate continuity as a conditioned stream rather than a persisting self. Death is read as dissolution, not annihilation; what carries forward are causal dispositions (saṅkhārā), not identity. The discussion clarifies the roles of bhava (becoming), duḥkha, and the unconditioned, and reviews classical images that convey presence without reification. Methodologically, it distinguishes heuristic comparisons with science from Buddhist soteriology, and notes the rarity and ethical opportunity of human life as enabling discernment and practice. The upshot is a synthetic account that links ontology, psychology, and ethics: continuity is causal and relational, moral agency is constitutive of future experience, and liberation consists in ending the grasping that sustains the cycle of becoming.